STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGEMBANGKAN MUTU SUMBERDAYA GURU - Moh. Samsul Arifin (Bajang Institute, 2022)
The Strategy Of Headmster Leadership In Developing The Quality Of Teacher Resource in MA Darut Tauhid Tanjungsari. The developing quality human resource especially the teacher is a necesasary for an institution of education that to survive during the the time, because the teacher in school institution is main part of achievement in school learning processs. The quality of school especially the students is often be engaged in the teacher quality. The purpose of this research,There are two objective would be investigated in this research that; to describe the srategies have done by headmster in developing the quality of teacher resource, to describe the implication headmaster leadershipin developingthe quality of teacher resource. After analyzing data resources, the case study of the research could be drawn, as foollow: the kind of teacher resource existance involve the number of teacher, the qualification of academic, and the development of academic. The effort and step strategies of principle in developing the quality of teacher resources are: (1) change the way thinking/positive character building through the education side, mentoring and teaching. These activities are accumulated in continued activity of degree study, training, formation of teacher assignment group; make the corpoeration with other institutions, giving an assignment, training and coaching. (2) make the vission and mission for purpose of MA Darut Tauhid Tanjungsari as the measure in developing the quality of teacher resource (3) the fullfillment of welfare either material or non material. The implication of principle leadership in development the teacher resource in MA Darut auhid Tanjungsari those are: (1) Listen the suggestion idea from the teacher and make communication with them (2) give an opportunities abd flexibilities for teacher who wants to continued their study in the degree (3) delegation of assignment for the other one if he could not be present (4) the fullfillment comfortable condition working togetherness. So, the research found that to create the quality of teacher, professionalism, commitment, and ethos working could be used the strategy of academy and using tho approaches buy aproach and make approach or comprhensive quality development srtategy or the developing the quality of teacher resource is literally